Sarsasapogenin reverses depressive-like behaviors and nicotinic acetylcholine receptors induced by olfactory bulbectomy. (3rd February 2017) - Feng, Bo; Zhao, Xiao-Yang; Song, Yi-Zhou; Liang, Wen-Na; Liu, Ji-Liang
Highlights: Sarsasapogenin reverses depressive-like behaviors in OB rat model. Sarsasapogenin modulating α4-nAChR and α7-nAChR expression in OB rat model. Sarsasapogenin reversed AChE activity in OB rat model. Abstract: Cholinergic signalling in the hippocampus may contribute to the aetiology of mood regulation. Antidepressants can reverse the increase in acetylcholinesterase (AChE) activity induced by olfactory bulbectomy. The activation of nicotinic acetylcholine receptors (nAChRs) also alleviates the symptoms of depression. This study advances the development of sarsasapogenin, which interacts with cholinergic signalling and has a favourable antidepressant profile in olfactory bulbectomised (OB) rats. We examined OB-induced changes in cholinergic signalling, as well as AChE, α4-nAChR, and α7-nAChR expression in the hippocampus. The results indicate that abnormal cholinergic signalling in the hippocampus contributes to the development of depression in the OB rat model. This depression may be alleviated following treatment with sarsasapogenin.